Mitochondrial sequence data clarify species concepts in the Cyclocephala mafaffa species complex (Coleoptera: Scarabaeidae: Dynastinae: Cyclocephalini) - Moore, Matthew R.; Harrison, Stefani M.; Cave, Ronald D.; Branham, Marc A. (Zootaxa, 2020)
The speciose genus Cyclocephala Dejean (Coleoptera: Scarabaeidae: Dynastinae: Cyclocephalini) has attracted research attention due to their diversity, agroeconomic importance, and floral visitation habits. Uniquely among Cyclocephala species, C. mafaffa Burmeister and C. deceptor (Casey), two nearly identical species, are diagnosed by a pronotal character: beaded or not beaded basal pronotal margin. We evaluated these morphological species hypotheses with a phylogenetic analysis of 12S and COI, neighbor-joining analysis, and several single-locus species delimitation procedures (automatic barcode gap analysis and three Poisson tree processes analyses). Together, these analyses supported the species concepts for C. deceptor and C. mafaffa. Delimitation procedures supported several distinct molecular operational taxonomic units among these taxa. We consider the separation of C. deceptor and C. mafaffa to be valid. We conservatively synonymize the West Indian subspecies C. mafaffa grandis Burmeister under C. mafaffa and offer a discussion on subspecific concepts in Cyclocephalini. We designate the lectotype of Stigmalia deficiens Casey. Implications of this study for other geographically widespread cyclocephalines or species with variable pronotal morphology are discussed.